PENGARUH INTERAKTIVITAS DAN VISUALISASI DALAM TEKNOLOGI PELAPORAN KEUANGAN DIGITAL TERHADAP KEPUTUSAN INVESTOR NON PROFESIONAL - Muchtar, Asyrafil; Novita, Novita (Universitas Nusantara PGRI Kediri, 2016)
This study employs information system theories (technology-to-performance chain) to examine link between characteristics of digital financial reporting technology (interactivity and visualization) and task requirements in a financial analysis context, and the impact of that link on non-professional investor`s decision. This research was conducted to accounting students, samples taken 49 respondents with purposive sampling method. Data were collected by questionnaires using a five-point Likert scale, to measure 32 indicators. The analysis technique used Partial Least Square (PLS). These results indicate that perceived interactivity and perceived visualization give the positive effect, but not significant on perceived performance. On the other hand, task-technology fit and perceived usefulness give the positive and significant effect in mediating perceived interactivity and perceived visualization against perceived performance. This study result shows the importance of digital financial reporting for non-professional investor decision